Treatment results of hip fractures in children - Yilmaz, Erhan; Karakurt, Lokman; Serin, Erhan; Güzel, Hikmet (My University, 2003)
Introduction: Paediatric hip fracture is rare and known to be associated with a high complication rate. Road traffic accident accidents and falls from a height were the main causative factors. Patients and Methods: This is a retrospective study of 15 children with traumatic fractures of the femoral neck and intertrochanteric region over a 6-year period. There were 9 boys and 6 girls and their mean age at the time of the injury was 6.3 years. The trauma type was high energy in all cases. By Delbet-Colonna classification, there was three type-2, six type-3 and six type-4 fractures. Spica cast treated four cases with no displacement of fracture and 11 cases with displaced fracture were treated by early decompression of the intercapsular hematoma, anatomic reduction and stable internal fixation. Results: Mean follow-up period was 44 months. At final follow-up, the results were assessed using Ratliff criteria and included 11 patients with good, 3 with fair and 1 with poor outcome. Fracture union was determined at average 7.2 weeks in patients treated by spica -cast and average 11 weeks in surgically treated patients. One patient had Ratliff type 1 avascular necrosis, 2 had coxa vara, 1 had non-union and subtrochanteric valgus osteotomy was performed for these complications. Discussion: In children's hip fracture; child's age, fracture type and level, fracture displacement was the designating factor for treatment method and prognosis of complications. Early open reduction and stable internal fixation of displaced hip fracture is an effective treatment method with low complication rate.
Çocuk kalça kiriklarinda tedavi? sonuçlarimiz
Keywords: Children; Hip fracture; Treatment